Tissue transglutaminase crosslinks ataxin-1: Possible role in SCA1 pathogenesis - D’Souza, D.R. (2006)
Transglutaminase type 2 (TG2) has recently been implicated in crosslinking of mutant huntingtin protein into aggregates. Here we show that TG2 also crosslinks spinocerebellar ataxia-1 (SCA1) gene product ataxin-1. HeLa cell lysates expressing GFP tagged ataxin-1 with 2, 30 or 82 glutamines showed covalent crosslinking of ataxin-1 when incubated with exogenously added TG2. This crosslinking was inhibited by TG2 inhibitor cystamine. SCA1 transgenic mice which overexpress the mutant ataxin-1 in cerebellar Purkinje cells showed elevated nuclear TG2 in the absence of ataxin-1 nuclear aggregates. The addition of purified TG2 to the nuclear extracts or addition of SCA1 nuclear TG2 to GFP-Q82 HeLa cell lysates resulted in the formation of insoluble aggregates. These data indicate that ataxin-1 is a substrate of TG2. Further, in SCA1 TG2 may translocate to the nucleus in response to nuclear accumulation of mutant ataxin-1 at early stages of the disease.